The perception of disability by community groups: Stories of local understanding, beliefs and challenges in a rural part of Kenya. - Karen Bunning; Joseph K Gona; Charles R Newton; Sally Hartley (PLoS ONE)
Cultural narratives on disability have received much attention over the past few decades. In contexts of poverty, limited information and everyday challenges associated with having, or caring for someone with a disability, different understandings have emerged. A project was set up to promote disability awareness in neighborhood communities in a rural part of Kenya, using a process of reflection and education. This paper reports on the first aspect-reflection. The aim was to investigate local understanding of disability as a co-constructed concept. The research questions were: 1. What cultural beliefs shape local understanding of disability? 2. What challenges are perceived to be associated with disability? A phenomenological approach was adopted. Focus group discussions were conducted with twenty-one community groups involving 263 participants and audio-recorded. The data were transcribed and thematic analysis was carried out. Visual maps were created to illustrate any interconnections, before establishing the final conclusions. Local beliefs attributed disability to: human transgression of social conventions, particularly concerning inappropriate family relations, which invoked a curse; supernatural forces affecting the child; the will of God; unexplained events; and biomedical factors. Challenges associated with disability related to the burden of caregiving and perceived barriers to inclusion, with stress as a shared bi-product. Local understanding of disability in this rural part of Kenya demonstrated overlapping explanations and plurality of beliefs. Two possible interpretations are offered. Firstly, oscillation between explanatory lines demonstrated instability, affecting broader acceptance of disability. Secondly, and more positively, in the face of challenges, the desire to make sense of the existing situation, reflected a healthy pluralism.